Reaction of Aspirin with Fecapentaene-12: A Possibility for Aspirin to Make Fecapentaene-12 Lose its Mutagenecity - KASSAEE, M.Z.; BEKHRADNIA, A.R.; ARSHADI, S. (Asian Journal of Chemistry, 2010)
While the controversy continues over the carcinogenicity of fecapentaene-12 (Fp-12), as a potent colorectal mutagen, and while reports on reducing the risk of colon cancer by consumption of aspirin are still widespread, our HF and B3LYP calculations indicate the possibility of the loss of mutagenecity of Fp-12 through its reaction with aspirin, where an acetyl transfer from aspirin to a primary or secondary hydroxyl group of Fp-12 appears exothermic.